Modul Pembelajaran Internet Of Things (Iot) Berbasis Obe Sebagai Modul Pembelajaran Revolusioner Taruna Teknik Listrik Bandara Politeknik Penerbangan Surabaya - Kabul Yunior, Yudhis Thiro; Subagyo, Edwardo (Politeknik Penerbangan Surabaya, 2025)
Internet of Things (IoT) is a primary need that has been widely used in various fields, including health, education, energy, transportation, housing, agriculture, livestock and the general environment. The development of industry and technology in the field of education continues to change. The world of education is currently faced with an era of digital disruption, or in the industry known as